“This spirit, when you feel it, it is always very cool…”: How cultural atmospheres work and why do we like them - P. S. Kupriyanov; M. L. Lurie (Шаги)
The paper, based on field research into cultural practices and institutions in several Russian cities (2019–2021), is the first attempt to describe and conceptualize atmosphere as a special mode of cultural production and consumption. The authors argue that atmosphere is an important element of modern cultural industry and can provide a special kind of cultural pleasure. The phenomenon of “cultural atmospheres” is considered within the field of atmosphere studies that has become widespread in recent years in philosophy, the humanities and the social sciences. In this theoretical context the research focus is set using key properties of the atmosphere phenomenon such as material nature and supermaterial effects, homogeneity, affectivity, lack of distance between the object and the subject, etc. The authors analyze the reflections and representations of their informants’ cultural life experience and show that atmosphere appears in discursive constructions not only as a characteristic of a certain place or event, but also as an independent source of affects, impressions and pleasures expected from culture. The atmosphere mode of culture consumption, implying relevant attunements provided by the perceiving subject’s work of imagination and cultural experience, free him from the “cultural consumption” imperative understood as the acquisition of a readymade product. One of the authors’ hypotheses is that it is this quality that gives cultural atmosphere a special charm.